PELATIHAN CANVA UNTUK PEMBUATAN BAHAN AJAR BAGI MAHASIWA DAN GURU PENDIDIKAN MATEMATIKA - Sari, Nenden Mutiara; Supianti, In In; Sartika, Nenden Suciyati; Pratidiana, Deni; Yunitasari, Ika; Nurhayarti, Siti (Mitra Mahajana: Jurnal Pengabdian Masyarakat, 2024)
This training is motivated by the advantages of canva as a graphic design tool that facilitates the creation of engaging and effective digital teaching materials. With its intuitive features, Canva offers an innovative solution for developing educational content that can enhance student engagement, highlighting the need for teacher training. This training aims to enhance teachers' skills in using Canva to create appealing and interactive instructional materials and evaluate its impact on the quality of educational content. The training involved 51 participants, consisting of mathematics teachers within the scope of the West Bandung Regency Education Office and students from the Master of Mathematics Education program. The method used was Participatory Action Research, involving the active participation of participants in the learning and evaluation process. The training was conducted in a hybrid format, combining face-to-face and online sessions for greater flexibility and wider reach. Evaluation results indicated that teachers' ability to create teaching materials using Canva significantly improved, with an average score above 80. Discussion of the results revealed that this training was effective in enhancing teachers' skills and had a positive impact on the quality of instructional materials. This activity concludes that the Canva training successfully achieved its objectives, although challenges such as time constraints and access issues need to be addressed. Recommended follow-up actions include enhancing technical support and extending the training duration to maximize benefits for participants in the future.